GIS-Based Decision-Support Program for Planning and Analyzing Short-Wood Transport in Russia - Yuri Gerasimov; Anton Sokolov; Timo Karjalainen (University of Zagreb, Faculty of Forestry, 2008)
The purpose of this study is to research the effects of different concentrations of mineral and biodegradable oils for chainsaws on seedling growth of pedunculate oak (Quercus robur L.) during two-year vegetation period. The paper also examines the influence of the above mentioned oils and their concentrations on the development of the seedling root system at the end of the second vegetation. Tests were carried out in forest nurseries on seven 1 m2 plots. Three plots were treated; after the planting of the pedunculate oak acorns; with biodegradable oil in the concentrations of 0.1 L/m2; 0.2 L/m2; and 0.5 L/m2. The other three plots were treated with mineral oil of the same concentrations. The control plot received only seed sowing. The analysis of the root system of the two-year-old seedlings of pedunculate oak was carried out with WinRHIZO ProLA 2400 software. The SAS and Statistica 7 program packages were used for the statistic data processing and for determination of statistically significant differences among variables. Results showed that the lower oil concentration the larger root lengths. The lowest heights of the two-year-old pedunculate oak seedlings were measured from the test plots treated with mineral oil and the highest on those from the plots treated with bio-oil; although the heights of seedlings from the control plots were very close to heights of those treated with bio-oil. Keywords: Extraction of short-wood from harvesting operations is becoming common practice in Russia. Logging companies are faced with a large number of options for short-wood transport, but they have limited knowledge of logistics potential. Developed GIS-based decision support program is a unique tool assisting logging companies in making comprehensive decisions on organizational options for the most suitable short-wood transport. Application of the program allows to increase efficiency when introducing cut-to-length technology in Northwest Russia, decrease wood transport costs and improve utilization of short-wood truck ...